Epidemiologia da leishmaniose visceral canina no município de Pedro Leopoldo, Minas Gerais, 2003. - Liz Adhara Bavaresco de Naveda (2005)
The aim of this work was to evaluate the prevalence of Canine Visceral Leishmaniasis and describe the demographic and epidemiological profile of the canine population of the municipality of Pedro Leopoldo, in 2003. We conducted a sero-epidemiological survey to collect blood samples from dogs and have applied semi-structured, organized into four groups and visited at home residence. The group, consisting of 1240 dogs from urban and rural, Group B consists of 700 samples from dogs at home around the outbreaks, Group C with 134 samples collected during vaccination against rabies and canine and feline, Group D, consisting of 111 stray dogs. To estimate the prevalence in urban areas, 22 areas were considered Zoning. Data were stored in a database EPI INFO 6.04b. Positive dogs were spatially located with the aid of GPS (Global Positioning System), and georeferencing, conducted through the program AUTOCAD 2000. Most dogs are within the range was 1 to 3.9 years, indicating a young dog population with complete renewal cycle every seven to nine years. Seventy-six percent of dogs are kept confined in urban areas, while 77.8% remains loose in the rural area. The results revealed the following demographic indices canines: mortality rate of 11.6%, neonatal mortality rate 27.2% birth rate of 39.3%, vegetative growth of 0.5%. The different locations, both urban and rural, have lower rates dog / people you specify, and differentiated, the indexes recommended by WHO. The overall prevalence of the county for canine visceral leishmaniasis was 1.4%, ranging from 1.1% in urban areas to 4.2%. These results showed that the municipality of Pedro Leopoldo is a quiet, receptive and vulnerable to the zoonosis according to the official classification of the Ministry of Health The spatial distribution of cases is different and requires health measures according to each risk area . The knowledge gained about the epidemiology of canine visceral leishmaniasis in the municipality will establish effective strategies for the control actions in the district